Notes on the ecology of the avifauna of Chore, Department of San Pedro, Paraguay - Hayes, Floyd E. (1988)
We studied and compared the bird faunas of forest. cleared and marsh habitats at Choré. Department of San Pedro. Paraguay. Data on flock sizes relative abundance and habitat use are summarized for 141 species of birds. Forest habitats were more species rich and unique than cleared or marsh habitats. The proportion of species belonging to for foraging guilds varied between the different habitats. Gregarious species (mostly frugivores and camivores) usually occurred in clearings and marshes. and were relatively more abundant than non-gregarious species. Forest birds occurred singly or in pairs. but often joined interspecific foraging flocks. The proportion of birds in relative abundance categories did not vary between different habitats or foraging guilds.